2018
DOI: 10.1186/s40104-018-0255-z
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of mycotoxin biodegradation agent on zearalenone and deoxynivalenol toxicosis in immature gilts

Abstract: BackgroundThe current study was carried out to evaluate the effects of mycotoxin biodegradation agent (MBA, composed of Bacillus subtilis ANSB01G and Devosia sp. ANSB714) on relieving zearalenone (ZEA) and deoxynivalenol (DON) toxicosis in immature gilts.MethodsA total of forty pre-pubertal female gilts (61.42 ± 1.18 kg) were randomly allocated to four diet treatments: CO (positive control); MO (negative control, ZEA 596.86 μg/kg feed and DON 796 μg/kg feed); COA (CO + 2 g MBA/kg feed); MOA (MO + 2 g MBA/kg fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
(49 reference statements)
5
11
0
Order By: Relevance
“…Researches have indicated that oxidative stress plays critical roles in the cytotoxic mechanism of mycotoxins ( Hassen et al., 2007 ). It has been reported that ZEA can induce oxidative stress, which can cause damages to organs including the liver and kidney with subsequent changes in some enzymatic parameters and cells including cleavages of proteins, endogenous DNA lesions and lipid peroxidation in gilts ( Shi et al., 2018 ) and mouse ( Hou et al., 2013 ). SOD and GSH-Px as the key enzymes of antioxidant system can scavenge free radicals generated from oxidant stress, reduce oxidative damage, and maintain cell structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researches have indicated that oxidative stress plays critical roles in the cytotoxic mechanism of mycotoxins ( Hassen et al., 2007 ). It has been reported that ZEA can induce oxidative stress, which can cause damages to organs including the liver and kidney with subsequent changes in some enzymatic parameters and cells including cleavages of proteins, endogenous DNA lesions and lipid peroxidation in gilts ( Shi et al., 2018 ) and mouse ( Hou et al., 2013 ). SOD and GSH-Px as the key enzymes of antioxidant system can scavenge free radicals generated from oxidant stress, reduce oxidative damage, and maintain cell structure.…”
Section: Discussionmentioning
confidence: 99%
“…Results from our previous studies also demonstrated that the Bacillus subtilis ANSB01G could degrade ZEA efficiently by 84.6%, 66.3% and 83.0% in naturally contaminated corn, distiller's dried grains with soluble and commercial pig feed, respectively ( Lei et al., 2014 ). Furthermore, we found that B. subtilis ANSB01G culture could ameliorate the negative effects of ZEA on reproductive performance in the sexually-immature or pre-pubertal gilts ( Shi et al., 2018 ; Zhao et al., 2015 ), suggesting that B. subtilis ANSB01G might be a potential mycotoxin biodegradation agent (MBA) for detoxifying ZEA. However, whether a low dose of dietary ZEA (a little higher than the Chinese limited value of ZEA, 100 μg/kg) presents a toxic damage to gestation gilts, and the effect of B. subtilis ANSB01G culture on the oxidative stress and cell apoptosis responses induced by low-dose ZEA exposure have never been studied in first-parity gestation sows.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The whole follicular development process is accompanied by apoptosis, and the apoptosis of adult animal granulosa cells contributes to regulation of egg ovulation or occlusion (Liu et al, ; Majd, Azizian, Tabandeh, & Shahriari, ). Previous research reports that feeding diet contaminated with ZEA and DON simultaneously (596.86 μg/kg + 796 μg/kg) had detrimental effects on reproductive status of gilts (Shi et al, ). Research has shown that deoxynivalenol adding to the bovine ovary of theca cells in vitro increased the apoptosis of bovine ovary theca cells and reduced steroid production (Guerrero‐Netro, Estienne, Chorfi, & Price, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to minimize the AFB exposure to prevent its detrimental effects. Recently, strategies, such as adsorption method, biodegradation and chemical treatment, have been proposed to alleviate the toxic effects of mycotoxins on livestock [3,[8][9]. Among them, supplementation of adsorbent is the most suitable approach to detoxify mycotoxins-contaminated feed, because it can bind and immobilize myco toxins to reduce toxic residues in feed and effectively prevent health risks in animals [10].…”
Section: Introductionmentioning
confidence: 99%